The Z.E.N Empowering sustainability through circular design and waste management / Efina Hamdan and Muhammad Yaster Yatimi Rusmadi - Hamdan, Efina; Rusmadi, Muhammad Yaster Yatimi (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The Faculty of Communication and Media Studies UiTM Negeri Sembilan Rembau Campus in collaboration with Majlis Rekabentuk Malaysia has recently hosted an event called “The Z.E.N (Zerowaste Environmental Network)” with the aim of raising awareness about the environmental impact of solid waste and pollution. The event also promoted the use of sustainable technologies by incorporating circular design principles. Taking place from June 23rd to June 25th at Institut Latihan FAMA in Port Dickson Negeri Sembilan, the program involved participation from the local community as well as final year students of Diploma in Communication and Media. The program featured a variety of engaging activities designed to empower participants with a deeper understanding of waste management and cultivate a sustainable mindset. These activities include a thought-provoking talk on circular design entitled “Don't Waste Your Waste”, a demonstration of 3D printing, a competition where participants could showcase their skills in transforming waste into reusable products and a beach cleanup initiative at Pantai Telok Pelandok in Port Dickson, in which contributed to the preservation and conservation of coastal ecosystems.